Risk Factors and Maternal Outcome of Secondary Post Partum Haemorrhage in Rangpur Medical College Hospital. - A one year study - Ferdousy, Hasina; Sultana, Ferdousi; Nahaer, Mst Kamrun; Begum, Mst Moon Moon; Begum, Mst Mahfuza (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Post partum haemorrhage (PPH) is one of the most common causes ofmaternal mortality worldwide. Primary PPH (which occurs within 24 hours of delivery) hasbeen studied a lot. But data regarding secondary PPH (which occurs 24 hours after deliveryupto to 6 weeks post partum) is sparse. Our aim was to find out the risk factors and maternaloutcome of secondary PPH. Materials and Methods: A cross sectional analytic study of 32 cases admitted with secondaryPPH in Gynae and Obstetric department of Rangpur Medical College Hospital during 1 yearstudy period was carried out. Result: Frequency of secondary PPH was 0.58%. Mean age of the patient was 25.23±2.79years; 22(69%) patients were multi para; 17 (53%) patients had education up to primarylevel. Maximum patients [18 (56%)] were from low socio economic status. Mean time ofpresentation was 13.5±2.78 days after delivery; 14(44%) patients delivered vaginally and18(56%) patients delivered by caesarean section. Most of the vaginal delivery 9 (28%) wereconducted by untrained dai or other family member. Among 32 patients, 31 were referredfrom outside the Hospital. Retained bits of placenta was the leading cause (15,47%) andcaesarean wound dehiscence was the second cause (13,41%); 13 (40%) patients had feveron presentation. All were anemic with mean hemoglobin concentration 7.4±1.4gm and 24(75%) of them required blood transfusion. Four patients was in shock. Antibiotic was givento all patients. DE&C was done in 15(47%) cases and laparotomy followed by total abdominalhysterectomy was done in 12 cases and repair in 1 case. Among 15 patients who underwentsurgical evacuation there was histological evidence of placental tissue in only 6(40%) patients. Conclusion: In present study retained bits of placenta and caesarean wound dehiscenceare found as main cause of secondary postpartum hemorrhage So care should be takenduring active management of third stage of labour (AMTSL). Choosing appropriate suturematerial, maintaining personal hygine of patient and sterility of operation theate, usingappropriate antibiotic to combat microbials and last but not list improving skillness of surgeonare the key to reduce the rate of secondary PPH. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 107-112